Strange-pulsar evolution and soft γ-repeaters - Horvath, Jorge Ernesto (1993)
Soft γ-repeaters are puzzling sources which produce γ-transients, and which have been tentatively identified as a separate subclass from sources which produce «classical» γ-bursts. We sketch the features of a model for soft γ-repeaters based on the evolutionary history of strange pulsars. It is shown that the main features of soft γ-repeaters can be explained by strange-pulsar evolution